THE INFLUENCE OF PRODUCT QUALITY, PRICE, STORE ATHMOSPHERE, AND PROMOTION EFFECTIVENESS ON CONSUMER PURCHASE DECISION OF FLINDERS LANE ESPRESSO MANADO - Hidayat, Priscillia Helena Maria (Sam Ratulangi University, 2015)
ABSTRACT Â Culinary industry already became one of the most industry that are developing right now. The study object is Flinders Lane Espresso Manado. The study aims to analyze the product quality, price, and promotion effectiveness to consumer purchase decision partially and simultaneously. 43 customers of Flinders Lane Espresso Manado were surveyed as respondents. As a result, the customer have realized that for any restaurant it is become an important thing to have a good quality of their product also combine it with an affordable price. Then, the customer really attracted with the quality of the product and less attracted with the store athmosphere. So as the recommendation for Flinders Lane Espresso, they should change the arrangement of Flinders to have a better relationship with the customer and for the better benefit for Flinders itself. Keywords: Product Quality, Price, Store Athmosphere, Promotion Effectiveness, Consumer Purchase Decision